The Content Validity and Interrater Reliability of Nursing Outcome Classification Self-Care for Toileting among Children with Physical Disabilities - Meisyarah, Yogi Hasna; Hartini, Sri; Haryanti, Fitri (Nurse Media Journal of Nursing, 2021)
Background: Nursing Outcome Classification (NOC) Self-care for Toileting is an instrument for measuring the abilities of toileting self-care among children with physical disabilities. However, there has been no cultural adaptation in the Indonesian context, especially among children with physical disabilities, so that the validity and inter-rater reliability of the instrument has not been reported. Testing the content validity and interrater reliability of this instrument is necessary so that it could be used to measure the ability of toileting self-care.Purpose: This study aimed to examine the content validity and inter-rater reliability of NOC Self-care for Toileting among children with physical disabilities.Methods: This was a descriptive quantitative non-experimental research with a cross-sectional design. In the content validity test, this study employed seven experts teaching in nursing academies with a minimum degree of S2/specialist and had the experiences in basic nursing to assess the validity of NOC Self-care for Toileting. As for the inter-rater reliability test, this study involved two raters of nursing students who have passed block 2.4 lecture on â€œGrowth and Developmentâ€ and 36 children with physical disabilities at a Special School in Bantul, Yogyakarta. The validity test was analyzed using CVR, CVI, and Aikenâ€™s V indexes, while the inter-rater reliability test was analyzed using Kappa and percent agreement.Results: The validity test showed the CVR value range of 0.71-1.00, the CVI value of 0.91, and the V coefficient range of 0.86-1.00. In the inter-rater reliability test, the Kappa value obtained was 0.958, and the percent agreement value was 97.22% for all indicators of NOC Self-care for Toileting.Conclusion: NOC Self-care for Toileting is a valid and reliable instrument for measuring the abilities of toileting self-care among children aged 6-18 with mild to moderate degrees of physical disabilities. Further research can be conducted by involving different respondents and cultures with more than two raters if possible.